2018
DOI: 10.1016/j.ridd.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the association between vocalizations and expressive language in children with autism spectrum disorder

Abstract: Young children with ASD demonstrate a strong association between vocalizations and expressive language skills. Future experimental studies should investigate causal relations to guide intervention development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 52 publications
0
12
0
3
Order By: Relevance
“…In contrast, the significant correlation between early consonant inventory and expressive language growth seen in Yoder et al (2015) was replicated in this sample. This adds to prior emerging evidence that speech production abilities are related to expressive language development in autistic preschoolers (McDaniel et al, 2017) and that speech production is worthy of further consideration when devising interventions (e.g. Chenausky, Norton, Tager-Flusberg & Schlaug, 2018).…”
Section: Confirmatory Analysesmentioning
confidence: 61%
See 1 more Smart Citation
“…In contrast, the significant correlation between early consonant inventory and expressive language growth seen in Yoder et al (2015) was replicated in this sample. This adds to prior emerging evidence that speech production abilities are related to expressive language development in autistic preschoolers (McDaniel et al, 2017) and that speech production is worthy of further consideration when devising interventions (e.g. Chenausky, Norton, Tager-Flusberg & Schlaug, 2018).…”
Section: Confirmatory Analysesmentioning
confidence: 61%
“…Investigations of infant siblings of autistic children (who have a higher chance of obtaining an autism diagnosis) also indicate early differences in vocalization rate and quality (Chenausky et al, 2017; Patten et al, 2014; Paul et al, 2011). A recent meta-analysis concluded that pre-verbal vocalizations are correlated with concurrent and later expressive language in young autistic children (weighted effect size of r = 0.50, McDaniel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder is a neurodevelopmental disorder commonly associated with verbal and communicative dysfunctions (Mcdaniel et al, 2018). In three studies identified in this review, alteration of language task-related coherence was associated with ASD (Righi et al, 2014;Kovelman et al, 2015;Mamashli et al, 2017).…”
Section: Results From Coherence In Clinical Populationmentioning
confidence: 87%
“…Echolalia was also tracked during the reading of the e-books and during the question periods, as it can indicate engagement and verbal language development (Charlop, 1983; McDaniel et al, 2018). Echolalia was recorded in ‘instances’ and not duration; one instance was defined as 15 seconds or more of the echolalic behavior; a break for three or more seconds was required before another instance could be counted.…”
Section: Methodsmentioning
confidence: 99%